Analisis Trend Topik Pengembangan Rekayasa Perangkat Lunak dalam mendukung Strategi Kurikulum Perguruan Tinggi - Bahruni Bahruni; Fathurrahmad Fathurrahmad (KITA Institute, 2019)
The development of software becomes important now and almost every point of view of our lives, many trends in various countries of the world in 2018 and will be interesting to follow in the following year for educational software-related developers. This study aims to analyze the relevance of the subject matter to the trend of device development research topics in order to produce sequential research between software development practicum subjects and trending topics in the world. The methodology used is a qualitative descriptive method used in analyzing the compatibility between courses, with trends in computer learning topics at the world level. Data collection is carried out through documents related to the outline categorized into 2 (two) groups. The first group deals with information relating to research trends related to publications in the journal Web of Science, SINTA, and Final Projects (TA) for Students. AMIK Indonesia. Relevance between AMIK Indonesia subject matter material and trends in relevant and supporting research topics for practicum material As a qualification of relevance for the category of high relevance with a value of 75% and above only 4 subjects, 7 moderate categories with a value of 55% to 74%, and 21 subjects with a low level of relevance, the findings that can produce material for the development of course material by supporting lecturers in each subject are specific to trending topics that are irrelevant or not supported by practicum courses that will have a positive influence on improvement quality.